Fixation Patterns of Chinese Participants while Identifying Facial Expressions on Chinese Faces - Xia, Mu; Li, Xueliu; Zhong, Haiqing; Li, Hong (Frontiers in Psychology, 2017)
Two experiments in this study were designed to explore a model of Chinese fixation with four types of native facial expressions—happy, peaceful, sad, and angry. In both experiments, Participants performed an emotion recognition task while their behaviors and eye movements were recorded. Experiment 1(24 Participants, 12 men) demonstrated that both eye fixations and durations were lower for the upper part of the face than for the lower part of the face for all four types of facial expression. Experiment 2(20 Participants, 6men) repeated this finding and excluded the disturbance of fixation point. These results indicate that Chinese participants demonstrated a superiority effect for the lower part of face while interpreting facial expressions, possibly due to the influence of eastern etiquette culture.